Evaluation of simultaneous incidence of head space and temperature on biochemical methane potential in food waste. Issue 1 (1st January 2020) - Casallas-Ojeda, Miguel R.; Marmolejo-Rebellón, Luis Fernando; Torres-Lozada, Patricia
Abstract: The anaerobic digestion (AD) of food waste (FW) has been recognised as a low-cost and high-efficiency alternative that mitigates the impacts of the final disposal of FW, while facilitating the production of high value-added by-products, such as biogas and digestate. In this study, the simultaneous incidence of two significant variables in the AD of FW were evaluated: the temperature (20, 35 and 55 °C), which affects the kinetics of the process, and the head space (20, 35 and 50%), which can affect the pH and therefore the biochemical methane potential (BMP). A composite central design was used, and response surface methodology (RSM) and kinetic models (the first-order and Gompertz models) were used to analyse the process. At higher temperatures and smaller head spaces, inhibition phenomena were reduced by the consumption of bicarbonate alkalinity and decreasing the pH, resulting in a higher process performance. The optimal conditions were a temperature of 48.9°C and a head space of 20%. The Gompertz kinetic model fit the process dynamics better and with a lower error than the first-order model.